2005
DOI: 10.1007/s10670-004-0602-7
|View full text |Cite
|
Sign up to set email alerts
|

Putnam and Constructibility

Abstract: I discuss and try to evaluate the argument about constructible sets made by Putnam in Ô'Models and Reality'Õ, and some of the counterarguments directed against it in the literature. I shall conclude that Putnam's argument, while correct in substance, nevertheless has no direct bearing on the philosophical question of unintended models of set theory.Erkenntnis (2005) 62: 395-409 Ó Springer 2005

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…5. 35 In general, a majority of researchers agree that this problem is solvable by moving to a class theory (of Kelley-Morse)-due to (Bellotti, 2005;Button, 2011). 36 Since some conclusions elaborated for difficulty D1 appear to be useful by difficulty 3, we consider it achronologically before difficulty 2.…”
Section: Moment Of Rejecting Realism: a Perspective Of The Putnam The...mentioning
confidence: 99%
See 4 more Smart Citations
“…5. 35 In general, a majority of researchers agree that this problem is solvable by moving to a class theory (of Kelley-Morse)-due to (Bellotti, 2005;Button, 2011). 36 Since some conclusions elaborated for difficulty D1 appear to be useful by difficulty 3, we consider it achronologically before difficulty 2.…”
Section: Moment Of Rejecting Realism: a Perspective Of The Putnam The...mentioning
confidence: 99%
“…The main goal of this article is to propose a meta-reconstruction of Putnam's semantic anti-realism and his model-theoretic argument-due to its exposition in Putnam (1980, Footnote 3 continued against Putnam's intentions. This critique met a reaction in Bellotti (2005). Many authors, such as Benacerraf and Wright (1985) and Bays (2001Bays ( , 2007, found Putnam's "Just-More-Theory" postulate-as a remedy for these difficulties-entirely question-begging.…”
Section: The Goals and Structure Of The Articlementioning
confidence: 99%
See 3 more Smart Citations